2015
DOI: 10.1007/s11060-015-2009-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function and quality of life in patients with newly diagnosed brain metastasis after treatment with intra-operative cesium-131 brachytherapy: a prospective trial

Abstract: Intraoperative permanent Cesium-131 (Cs-131) brachytherapy can provide a viable alternative to WBRT with excellent response rates and minimal toxicity. This study reports the results of the prospective trial of the impact of intraoperative Cs-131 on neurocognitive function and quality of life (QoL) in patients with resected brain metastases. Between 2010 and 2012, 24 patients with newly diagnosed metastasis to the brain were accrued on a prospective protocol and treated with Cs-131 brachytherapy seeds after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Early postresection initiation of radiation-when residual tumor burden is minimal-could evince a relatively higher therapeutic ratio in rapidly proliferating tumors. 6,15 BT using a low-energy (i.e., short-range) isotope exposes less normal tissue to radiation than EBRT techniques, 31,34 and it may limit neurocognitive deficits 28,33 while allowing a higher local radiation dose. 34 Radiation source placement under intraoperative visualization also should allow a more precise identification of the area at risk than the postoperative imaging utilized for EBRT treatment.…”
mentioning
confidence: 99%
“…Early postresection initiation of radiation-when residual tumor burden is minimal-could evince a relatively higher therapeutic ratio in rapidly proliferating tumors. 6,15 BT using a low-energy (i.e., short-range) isotope exposes less normal tissue to radiation than EBRT techniques, 31,34 and it may limit neurocognitive deficits 28,33 while allowing a higher local radiation dose. 34 Radiation source placement under intraoperative visualization also should allow a more precise identification of the area at risk than the postoperative imaging utilized for EBRT treatment.…”
mentioning
confidence: 99%
“…We found that there was a statistical improvement in overall FACT-Br score at 4 and 6 months of follow-up when compared to baseline (162 vs. 143, p = 0.004; 164 vs. 143, p = 0.005, respectively), with an insignificant trend towards improvement at 2 and 12 months (154 vs. 143, p = 0.067; 159 vs. 149, p = 0.4, respectively). MMSE score was statistically improved at 4 months and up to 12 months compared to pre-treatment MMSE (30 vs. 29, p = 0.017; 30 vs. 29, p = 0.001, respectively) [21]. …”
Section: Discussionmentioning
confidence: 99%
“…However, in general, local control refers to restriction of disease to the area immediately surrounding the resection cavity, while distant recurrence defines disease recurring or progressing outside the immediate area of the resection cavity. A notable exception included studies by Wernicke et al and Pham et al who reported 100% rate of local control, but some instances of regional recurrence defined as dural-based enhancement were > 5 mm from the resection cavity [10,11,12,13]. Summative assessments of treatment efficacy and toxicity were completed based on radioisotopes and brachytherapy techniques used in various studies.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on 131 Cs brachytherapy for treatment of brain metastases have been performed by Wernicke and colleagues including 24 patients in two studies and 42 in another research. Patients were treated with local resection, followed by implantation of permanent 131 Cs seeds (Table 2) [10,11,12,13]. These studies reported 100% of local brain control, low rates of regional recurrence, and distant progression within the brain, with no cases of radiation necrosis and minimal post-operative complications (Tables 4 and 6).…”
Section: Cesium-131mentioning
confidence: 99%
See 1 more Smart Citation